Cybersecurity in Asean: the effectiveness of the initiatives taken by Asean in securing the region / Nuralya Balqish Johari - Johari, Nuralya Balqish (2018)
Since the late 20th century, the world has experienced a great revolutionary in the area of information technology. This can be seen where cyber space has becoming necessity for individuals’ life, governments, business and also organizations. According to Internet World Stats (2017), the internet users in Asia region in as of June 2017 is 49.7%.This is because, cyber space has become an essential platform to support national growth due to its borderless connection. However, this borderless connection throughout the world could create a lot of security problem (Lalitha, 2012). This can be seen when the problem of cyber-attacks is currently increasing its seriousness in the world. Due to this problem, cyber security has becoming a critical research and development in the world and also in the Association of Southeast Asian Nations (ASEAN) region. Over the past 50 decades since ASEAN is founded, the problem of cybercrime often occurs and increasing in the ASEAN region. Due to this, since the problem is very serious as it can threaten the security of the region, a lot of cyber security initiatives has been taken by ASEAN (ASEAN, 2017). Hence, this study aim to examine the effectiveness of cyber security initiatives taken by ASEAN in securing the region. The study focused on three section, which is first, to identify the cyber security initiatives implemented in ASEAN, second to examine the effectiveness of cyber security initiatives in ASEAN by looking on each member states and lastly is to identify the obstacles faced by ASEAN and measures taken to counter cyber threats. It is hope that the study can contribute to the improvement of the effectiveness of cyber security initiatives by ASEAN in order to secure the region.